2015
DOI: 10.1016/j.invent.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

From black box to toolbox: Outlining device functionality, engagement activities, and the pervasive information architecture of mHealth interventions

Abstract: mHealth interventions that deliver content via mobile phones represent a burgeoning area of health behavior change. The current paper examines two themes that can inform the underlying design of mHealth interventions: (1) mobile device functionality, which represents the technological toolbox available to intervention developers; and (2) the pervasive information architecture of mHealth interventions, which determines how intervention content can be delivered concurrently using mobile phones, personal computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 90 publications
(108 reference statements)
0
86
0
Order By: Relevance
“…Smartphones enable on-the-go delivery of intervention content via push notifications that can be delivered at convenient times for the user or when specific intervention content is needed [10,11]. Notifications can also prompt access to more intensive support provided by other platforms [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones enable on-the-go delivery of intervention content via push notifications that can be delivered at convenient times for the user or when specific intervention content is needed [10,11]. Notifications can also prompt access to more intensive support provided by other platforms [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Through this study, we learned valuable lessons about how to improve processes and procedures for enrolling participants and create and maintain relationships between study staff and participants in order to minimize attrition in future studies. Retention and engagement are pressing issues in mHealth research, with many suggested techniques for increasing engagement, including more interactivity, changing content, and gamification [98][99][100]. Methods for improving study retention include more frequent contact (texting) throughout the study, using a more stringent enrollment process, and providing escalating incentives for each follow-up assessment [101][102][103].…”
Section: Limitationsmentioning
confidence: 99%
“…Nowadays, the challenges and demands that adolescents face create a need for innovative strategies for the promotion of healthy behaviours with the inclusion of mHealth technologies (Kim & Xie, ). mHealth interventions have emerged due to the ubiquity use of mobile devices, mostly smartphones, making it possible to deliver meaningful health information in people's everyday activities (Danaher, Brendryen, Seeley, Tyler, & Woolley, ; European Commission, ). This concept of mobility is central for a participatory health care (Cameron, Ramaprasad, & Syn, ), presenting diverse health intervention opportunities that range from disease management to smoking cessation, or weight loss (Afshin et al, ; Bert, Giacometti, Gualano, & Siliquini, ; Sousa, Fonseca, Gaspar, & Gaspar, ).…”
Section: Introductionmentioning
confidence: 99%